Synthesis of novel and potent vorapaxar analogues. Issue 12 (2nd March 2016) - Knight, Emily; Robinson, Eifion; Smoktunowicz, Natalia; Chambers, Rachel C.; Aliev, Abil E.; Inglis, Graham G.; Chudasama, Vijay; Caddick, Stephen
Abstract : Unlocking novel and potent vorapaxar analogues by functionalisation of previously unexplored positions on the parent vorapaxar scaffold. Abstract : Vorapaxar is a first-in-class PAR-1 antagonistic drug based on the ent -himbacine scaffold. Detailed in this article are enantioselective and racemic routes to various novel vorapaxar analogues. Biological testing revealed these compounds to have moderate to excellent potencies against PAR-1 with the most potent analogue demonstrating an IC50 of 27 nM.